Combination of reduced levels of serum albumin and alpha-2-macroglobulin differentiates newly diagnosed pulmonary tuberculosis patients from patients on chemotherapy (2009)
Pulmonary tuberculosis (PTB) is global disease affecting about one third of the world’s population with its attendant mortality and morbidity. Acute phase proteins have been used in monitoring the progression of infections but not in relation to PTB in this environment. The levels of total protein, albumin, α-2-macroglobulin, transferrin, and haptoglobulin were determined in 23 patients with PTB and 17- age / sex matched PTB-free controls using spectrophotometric and immunodiffusion methods respectively. The result showed that α-2-macroglobulin was significantly raised in PTB patients compared with controls (p<0.001), while the levels of transferrin and albumin were significantly reduced in PTB patients compared with the controls (p<0.001,0.000 respectively). The levels of α-2-macroglobulin and albumin were significantly raised in PTB patients on treatment compared with newly diagnosed PTB patients (p=0.05, p=0.01 respectively). The combination of reduced levels of albumin and α-2-macroglobulin may be used to differentiate newly diagnosed PTB and those on chemotherapy